2022
DOI: 10.1111/bjso.12562
|View full text |Cite
|
Sign up to set email alerts
|

A history of collective resilience and collective victimhood: Two sides of the same coin that explain Black Americans' present‐day responses to oppression

Abstract: Collective victimhood and collective resilience are two sides of the same coin. However, most literature to date has focused on the experiences and consequences of collective victimhood. In the present research, we focused on the ex-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 79 publications
1
4
0
Order By: Relevance
“…Both participants describe the positive adaptations to hardship the ingroup has experienced as examples of ingroup power. This is consistent with scholarship emphasizing duality in oppressed groups’ experiences of both oppression and strength (e.g., D. V. Mosley et al., 2020; Quayle & Sonn, 2019; Selvanathan et al., 2022; Vollhardt & Nair, 2018). By looking beyond the collective victimization experiences that threaten groups’ agency (Shnabel & Nadler, 2015), participants were able to maintain a sense of collective power.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Both participants describe the positive adaptations to hardship the ingroup has experienced as examples of ingroup power. This is consistent with scholarship emphasizing duality in oppressed groups’ experiences of both oppression and strength (e.g., D. V. Mosley et al., 2020; Quayle & Sonn, 2019; Selvanathan et al., 2022; Vollhardt & Nair, 2018). By looking beyond the collective victimization experiences that threaten groups’ agency (Shnabel & Nadler, 2015), participants were able to maintain a sense of collective power.…”
Section: Resultssupporting
confidence: 87%
“…Furthermore, participants’ lay theories of collective power also reflect some theoretical expositions on Black power (e.g., Collins, 2000; Ture & Hamilton, 1967). Our study therefore takes an important first step in integrating different theories of group‐based power and investigating their relevance to people's own understanding of power, among a structurally disadvantaged group with a long history of resistance and resilience (see also D. V. Mosley et al., 2020; Selvanathan et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…These findings align with studies documenting greater resilience and optimism among people of color than among White people in the United States during the pandemic (Graham et al, 2022). Future research should examine patterns and correlates of benefit finding across different racial and ethnic groups that have experienced discrimination in the United States to better inform agencies charged with supporting these communities during public health crises (Selvanathan et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that these narratives have different motivations and meaning for minority groups. For example, Selvanathan et al (2022) showed that historical narratives held by African-Americans tended to follow a progressive arc, beginning in experiences of victimisation and oppression, followed by instances of resistance and resilience. In this way, progressive narratives may serve a more specific identity-empowering function for minority groups, while still being critical and recognising the need for structural change (example response: 'As an African-American I can see our historical challenges, I can embrace our accomplishments and I can see the work that still needs to be in our quest to recognised as full Americans').…”
Section: Narrative and Identitymentioning
confidence: 99%